Implementation of Leadership Values in Pancasila Paradigm as Character Building Values - Zulfikar Putra; Farid Wajdi (Universitas Sebelas Maret, 2021)
The purpose of this study was to determine the implementation of leadership values in the Pancasila paradigm as a character-building value. This research uses descriptive qualitative type and literature study by applying the technique of observation, documentation, and interviews. The data analysis technique is done by categorizing and classifying based on the logical analysis, then interpreted in the context of the whole research problem. The findings of the research show that students of basic leadership training do not understand the values of leadership in an applicative manner, this can be seen by the incomplete understanding of leaders and leadership. This research is expected that students are able to implement leadership values in the context of the Pancasila paradigm through character building in everyday life.